Plantae Colombianae, V: Species nova generis Herrania Plantae Colombianae, V: Species nova generis Herrania - Schultes Richard Evans (Caldasia)
Recently, señor Gabriel Gutiérrez, Agrónomo Auxiliar de la Sección de Biología Vegetal, kindly submitted to me for study a collection of Herrania from Santander. It represents an interesting new species, the description of which is presented below.  A very complete series of field data accompanied the botanical specimen. These, as welh as the plant material, were sent in by Señor Jorge Ortíz Méndez, Ingeniero Agrónomo, Jefe de la Secretaria de Agricultura e Industrias in Bucaramanga. A number of these field data permit a more complete undertanding of certain parts of the plant than could be had from a study of the type alone.  It is with pleasure that I thank Miss Inés de Zulueta for her accurate drawings of the fruiting portions of this new species.<--> Recently, señor Gabriel Gutiérrez, Agrónomo Auxiliar de la Sección de Biología Vegetal, kindly submitted to me for study a collection of Herrania from Santander. It represents an interesting new species, the description of which is presented below. A very complete series of field data accompanied the botanical specimen. These, as welh as the plant material, were sent in by Señor Jorge Ortíz Méndez, Ingeniero Agrónomo, Jefe de la Secretaria de Agricultura e Industrias in Bucaramanga. A number of these field data permit a more complete undertanding of certain parts of the plant than could be had from a study of the type alone. It is with pleasure that I thank Miss Inés de Zulueta for her accurate drawings of the fruiting portions of this new species.